2017
DOI: 10.1111/cup.12904
|View full text |Cite
|
Sign up to set email alerts
|

MYB, CD117 and SOX‐10 expression in cutaneous adnexal tumors

Abstract: Expression of MYB appears limited to a small number of cutaneous adnexal tumors, including cylindromas, spiradenomas, ACCs, mucinous carcinoma, endocrine mucin-producing sweat gland carcinoma and some cases of EMPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…Benign adnexal tumors usually show a characteristic pattern of MYB expression in a cluster pattern in the central portion of the tumor aggregations. The successive loss of nuclear MYB expression is interpreted as a hint for malignant transformation 36. Evangelista et al recently confirmed the results of previous studies, showing homogeneous MYB positive clusters only in cylindromas and spiradenomas 30,32,36.…”
mentioning
confidence: 72%
“…Benign adnexal tumors usually show a characteristic pattern of MYB expression in a cluster pattern in the central portion of the tumor aggregations. The successive loss of nuclear MYB expression is interpreted as a hint for malignant transformation 36. Evangelista et al recently confirmed the results of previous studies, showing homogeneous MYB positive clusters only in cylindromas and spiradenomas 30,32,36.…”
mentioning
confidence: 72%
“…Our case adds to this list, and ancillary immunohistochemical marker studies performed out of academic interest highlight potential pitfalls with basaloid-appearing breast neoplasms. Recent investigations of MYB and SOX-10 expression in cutaneous adnexal tumors have shown 85% (17/20) immunohistochemical reactivity for both MYB and SOX-10 in cylindromas with SOX-10 studies showing more diffuse and intense staining patterns [ 35 ]. While SOX-10 is known to play an important role in melanocyte development and can be used as a diagnostic marker of malignant melanoma, this protein is less studied in tumors of the apocrine and eccrine sweat glands.…”
Section: Discussionmentioning
confidence: 99%
“…While SOX-10 is known to play an important role in melanocyte development and can be used as a diagnostic marker of malignant melanoma, this protein is less studied in tumors of the apocrine and eccrine sweat glands. Diffuse expression in cylindromas can be considered as a marker of myoepithelial differentiation [ 35 ]. While malignant transformation of cutaneous cylindromas is rare, reports of some cases do exist [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cutaneous adnexal tumors, in 2017 Evangelista and North reported SOX10 positivity in spiradenomas, cylindromas and mixed tumors, presumably because of myoepithelial differentiation commonly present in all of them; also they emphasized that SOX10 and CD117 appear to be important proteins for apocrine and eccrine sweat units. In the same study, all follicular tumors included were negative for SOX10 . Finally, SOX10 can be expressed in cutaneous myoepitheliomas …”
Section: Introductionmentioning
confidence: 89%